Epidemiology of Dysentery, Uganda, 2014-2018 - Maureen Nabatanzi; Benon Kwesiga; Lilian Bulage; Bernard Lubwama; Alex Riolexus Ario; Julie Harris (Journal of Interventional Epidemiology and Public Health)
ntroduction: Shigella dysenteriae infection (dysentery) is endemic in developing countries. In Uganda, dysentery is a priority disease for surveillance, however, there is a paucity of data on its magnitude and distribution. We used surveillance data to describe dysentery cases in Uganda, 2014-2018.